Quantitative and qualitative analysis of menus in Belo Horizonte (MG) (Research, Society and Development, 2022)
The study aimed to perform a quantitative and qualitative analysis of the menu and per capita within the University Restaurant Health campus of the Federal University of Minas Gerais (UFMG), located in Belo Horizonte, Minas Gerais. In the quantitative analysis, the 14-day lunch menu was calculated for analysis of total caloric value, quantity of macronutrients, saturated fats, fibers and total sodium. For qualitative analysis the Method of Qualitative Evaluation of the Preparations of the Menu (AQPC) was applied, considering parameters that allow an overall evaluation of the menu. It was found that the protein capsule presented a mean gross per capita value of 1320,40 ± 147,83 kcal, suitability of 1,54 carbohydrates, 2,43 proteins, 1,51 of lipids and 2,56 of fibers, while the vegetarian protein menu presented a mean gross per capita value of 1133,90 ± 116,12 kcal, suitability of 1,81 carbohydrates, 1,37 proteins, 0,83 lipids and 3,05 fibres. Qualitatively, both menus presented positive results for variety of colors, offer of vegetables, leafy and fruits, all markers of a healthy diet. However, frying was predominant as a technique of cooking vegetarian protein preparation, indicates monotomy and points to excessive use of oil. In this way, it is inmportant to plan for the promotion of a greater variety of vegetarian protein options, as well as awareness of the user of the RU campus Health of an adequate and balanced portion so that the meal, despite nutritionally rich, is in adequate quantities in order to avoid the excess of nutritional needs.